MiR-146a-5p engineered hucMSC-derived extracellular vesicles attenuate Dermatophagoides farinae-induced allergic airway epithelial cell inflammation - Liu, Jiaxi; Xu, Zuyu; Yu, Jinyan; Zang, Xiao; Jiang, Shangde; Xu, Shuyue; Wang, Wei; Hong, Shanchao (Frontiers in Immunology, 2024)
Allergic asthma is prevalent in children, with Dermatophagoides farinae (D. farinae) being a common indoor allergen. Current treatments for allergic airway inflammation are limited and carry risks. Mesenchymal stem cell-derived extracellular vesicles (MSC-EVs) show promise as a cell-free therapeutic approach. However, the use of engineered extracellular vesicles (EVs) for D. farinae-induced allergic airway epithelial cell inflammation remains unexplored. This study generated miR-146a-5p-engineered EVs (146a-EVs) from human umbilical cord mesenchymal stem cells (hucMSCs) and established D. farinae induced mouse and human bronchial epithelial cells allergic models. Treatment with hucMSC-EVs effectively reduced allergic inflammation, while 146a-EVs showed greater efficacy. The enhanced efficacy in alleviating allergic airway inflammation was attributed to the downregulation of interleukin-1 receptor-associated kinase 1 (IRAK1) and tumor necrosis factor receptor-associated factor 6 (TRAF6) expression, facilitated by miR-146a-5p. This downregulation subsequently led to a decrease in NF-κB nuclear translocation, which in turn resulted in reduced activation of the NLRP3 inflammasome and diminished production of inflammatory cytokines, including IL-6, TNF-α, pro-IL1β and pro-IL18. These findings highlight the potential of miR-146a-5p-engineered hucMSC-derived EVs as a cell-free therapeutic approach for D. farinae-induced allergic airway epithelial cell inflammation.